Manajemen dana desa di Desa Girirejo, Kecamatan Kaliangkrik, Kabupaten Magelang tahun 2018 - Anis Rahmawati; Hendrarto Hendrarto; Retno Dewi Pramodia Ahsani (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
This study discusses village fund management which was carried out in Girirejo Village, Kaliangkrik District, Magelang Regency in 2018. The purpose of this research is to identify and analyze village fund management in Girirejo Village by using management theory from G. R. Terry consisting of 4 aspects including; (1) Planning; (2) Organizing; (3) Direction; (4) Control. This study uses qualitative research methods with a case study approach. The results of this study village fund management in the village of Girirejo has been going well, seen from every aspect of management is in accordance with the objectives of the village fund program. In addition, village fund management in Girirejo Village has also involved the community in several activities. Even though it has been going well, the management of village funds in Girirejo Village still faces several obstacles, namely the problem of implementing activities that include issues of weather, materials and work fields that are difficult to reach so that it influences the management of village funds in Girirejo Village.DOI: https://doi.org/10.26905/pjiap.v4i2.3303